2021
DOI: 10.1021/acs.inorgchem.1c00079
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Power Factor and Figure of Merit of Cu2ZnSnSe4-Based Thermoelectric Composites by Ag Alloying

Abstract: The quaternary chalcogenide composites Cu 2 ZnSn 1−x Ag x Se 4 (0 ≤ x ≤ 0.075) have been successfully synthesized by high-temperature melting and annealing followed by hot-pressing. The phase structure of the bulk sample has been analyzed by powder X-ray diffraction and Rietveld refinement combined with Raman spectroscopy to confirm Cu 2 ZnSnSe 4 as the main phase with ZnSe and Cu 5 Zn 8 secondary phases. The thermoelectric properties of all specimens have been investigated in the temperature range of 300−700 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…The electrical resistivity of 600 °C sample exhibits semi-metallic behavior in the first half and metallic behavior in the second half as the values of electrical resistivity decrease with increasing temperature up to 473 K and then increase sharply with the rising temperature which probably be resulted from ionized impurity scattering; meanwhile the values of electrical resistivity of other samples show slight increase with the increasing temperature exhibiting degenerate semiconducting behavior [25]. Temperature dependence of electrical resistivity of 600 °C sample is different from other samples but is consistent with previous reports [8,9,19]. Furthermore, the electrical resistivity of the samples decreases with the increasing annealing temperature.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The electrical resistivity of 600 °C sample exhibits semi-metallic behavior in the first half and metallic behavior in the second half as the values of electrical resistivity decrease with increasing temperature up to 473 K and then increase sharply with the rising temperature which probably be resulted from ionized impurity scattering; meanwhile the values of electrical resistivity of other samples show slight increase with the increasing temperature exhibiting degenerate semiconducting behavior [25]. Temperature dependence of electrical resistivity of 600 °C sample is different from other samples but is consistent with previous reports [8,9,19]. Furthermore, the electrical resistivity of the samples decreases with the increasing annealing temperature.…”
Section: Resultssupporting
confidence: 89%
“…The Lorentz fit of Raman spectroscopy, shown in Fig. 2, depicts the major peak located at 181 cm -1 which is allocated to CZTSe main phase [4,19] and ZnSe secondary phase peaks located at 205 cm -1 at 252 cm -1 [20]. Furthermore, the presence of CuSe secondary phase present in XRD results is not detected in Raman Spectra, as a strong peak located at around 262 cm -1 associated with CuSe is not present in our Raman spectra [21][22][23], which may be due to the low concentration of CuSe phase.…”
Section: Resultsmentioning
confidence: 99%
“…[55] A few studies on the TE performance of kesterites in bulk form revealed improved properties when cation disorder is introduced, [56][57][58][59] and with Cu-doping, [60][61][62] especially for the selenide compound. [61,[63][64][65][66] In particular, they have been deemed promising materials for their exceptional TE performance over cost ratio, [60] thus making them particularly interesting for sustainable and low cost generation. Surprisingly, it emerges a substantial scarcity of TE investigation for the thin film configuration of these materials, [67,68] despite the vast knowledge acquired in their fabrication and PV characterization.…”
Section: Structural Optical and Compositional Characterization Of The...mentioning
confidence: 99%
“…This can be achieved by tailoring new TEMs using various strategies such as band engineering, 8,9 nanostructuring, 10–12 and alloying or substituting. 13–18…”
Section: Introductionmentioning
confidence: 99%